Estudio de un destino de cruceros a partir de la estimación del efecto multiplicador: caso Cozumel (México) - María de Jesús Moo Canul; Carlos Alonso Estrella Carrillo; Romano Gino Segrado Pavón; Lucinda Arroyo Arcos (Études Caribéennes)
Cozumel is Mexico's largest cruise port. According to the Ministry of Tourism of the State of Quintana Roo, Cozumel received 2,753,608 visitors in 2013. The aim of this study is to determine the multiplier effect of the consumption of these visitors. The multiplier effect of spending was determined by cross-tabulating information collected from 370 questionnaires in July and August 2014, linear regressions between spending at the target and the income level of cruise visitors, and the Marginal Propensity to Consume (MCO) indicator. Ordinary Least Squares and Error of Specification, t-test statistics and F-test were used to determine the statistical significance of the variables raised. The multiplier was determined by identifying the main sectors where visitors consume goods. The results show that spending by cruise visitors has a direct relationship with their income level, but it was not possible to obtain a representative for the R2 model, suggesting that there are other variables, not considered in this study, that have a greater impact in determining the amount of spending made.